Guided wave temperature correction methods in structural health monitoring - Salmanpour,MS; Sharif,khodaei; Aliabadi,MH (Journal of Intelligent Material Systems and Structures, 2016)
In this paper a method for addressing temperature effects using Lamb waves is developed withapplication to baseline comparison damage detection. The proposed method is based on baseline signal stretchwith an improved minimum residual allowing correction over a larger temperature range. The effectiveness ofthe proposed approach in detecting (artificial) damages is demonstrated experimentally over a large temperature.The method is also shown to accurately detect and localise a crack in an aluminium panel and actual impactdamage on a CFRP panel.